Green innovation risk index screening under the global value chain based on the group decision characteristic root method - Sun, Yingying (Frontiers in Environmental Science, 2023)
As there are a large number of risk factors affecting green innovation under the global value chain, the screening of risk indicators is a key link in developing green innovation activities. Through the analysis of the influencing factors of current green innovation risk, the primary index of green innovation risk is established. The group decision characteristic root method is used to identify the key importance of primary indicators of green innovation risk and construct the global value chain’s green innovation risk index system, which provides a scientific method and new ideas for measuring and evaluating green innovation risk in the global value chain. The empirical results of this paper are as follows: 1) green R&D risk measurement indicators under the global value chain include the proportion of global green R&D personnel investment, the proportion of global green R&D capital investment, the stability of global green R&D in manufacturing, the ease of international transfer of green technology, and the international protection of green technology patents; 2) Green manufacturing risk measurement indicators under the global value chain have seven risk factors: the proportion of global green manufacturing personnel investment, the proportion of global green manufacturing capital investment, the global green manufacturing product production scale, the global green manufacturing product quality performance level, the global outsourcing scale of green products, the global green manufacturing technology transformation degree of manufacturing industry, and the global green manufacturing cost increase; 3) green marketing risk measurement indicators under the global value chain have seven risk factors: the proportion of global green marketing personnel investment, the proportion of global green marketing capital investment, the international demand level for green products, the international market competition intensity of green products, the possession of green products to existing international marketing channels, the commercialization and internationalization level of green technology, and the intensity of green technical barriers to trade in the international community; and 4) green service risk measurement indicators under the global value chain have five risk factors: the proportion of global green service personnel investment, the proportion of global green service capital investment, the 1coverage of global green service outlets, the globalization level of global green product supply chain, and the global after-sales technical service capability of green products.